The determinants of capital structure for financially distressed listed companies in Malaysia - Shaminy, Ganesan (2020)
This study aims to examine the relationship between the determinants of capital structure and the financially distressed listed companies in Malaysia. There are 23 companies classified as financially distressed companies or fall under PN17 category included in this study and the data have been collected from journals articles, internet resources, and websites while for financial information annual reports of financially distressed companies were gathered from Bursa Malaysia. Descriptive analysis and multiple regression analysis used to explain the relationship between profitability, tangibility, growth, firm’s size, and intangibility of assets towards capital structure of financially distressed companies in Malaysia. The result shows that the capital structure of financially distressed companies in Malaysia have significant relationship with profitability, tangibility and firm’s size, while insignificant relationship with growth and intangibility of assets.